1995
DOI: 10.1128/iai.63.10.4072-4077.1995
|View full text |Cite
|
Sign up to set email alerts
|

Pseudomonas aeruginosa invasion of and multiplication within corneal epithelial cells in vitro

Abstract: Pseudomonas aeruginosa is usually considered an extracellular pathogen. Using assays to determine intracellular survival in the presence of gentamicin, we have previously demonstrated that P. aeruginosa is able to invade corneal cells during infectious keratitis in mice. In vitro, P. aeruginosa was found to enter the following cells: human corneal cells removed by irrigation; epithelial cells in the cornea of rats, mice, and rabbits; and primary corneal epithelial cells cultured from rat and rabbit eyes. The l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
90
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(96 citation statements)
references
References 14 publications
6
90
0
Order By: Relevance
“…Previous studies have shown that actin cytoskeleton disruption mediated via toxins such as cytochalasin D or latrunculin A or other TTSS effectors, e.g., ExoT and ExoS has significant invasion-inhibitory activity towards P. aeruginosa [7,30,[36][37][38]. Consistent with those earlier studies, ExoY-mediated actin disruption at 2 h coincided with inhibition of bacterial invasion for both adenylate cyclase active and inactive forms of the molecule.…”
Section: Discussionsupporting
confidence: 86%
“…Previous studies have shown that actin cytoskeleton disruption mediated via toxins such as cytochalasin D or latrunculin A or other TTSS effectors, e.g., ExoT and ExoS has significant invasion-inhibitory activity towards P. aeruginosa [7,30,[36][37][38]. Consistent with those earlier studies, ExoY-mediated actin disruption at 2 h coincided with inhibition of bacterial invasion for both adenylate cyclase active and inactive forms of the molecule.…”
Section: Discussionsupporting
confidence: 86%
“…Among the compounds acting on cytoskeletal structures, cytochalasins can prevent the uptake of microorganisms or inhibit intracellular bacterial multiplication (1. 3,4,10,12,15,16,28). An inhibiting effect on L. pneumophila internalisation in Acanthamoeba castellanii was reported by Moffat and Tompkins (23).…”
Section: Discussionmentioning
confidence: 81%
“…These were used to quantify the extent of bacterial invasion of HeLa cells. These assays were performed as described previously for assessing Pseudomonas aeruginosa invasion of epithelial cells (Fleiszig et al, 1995).…”
Section: Cell Infectionmentioning
confidence: 99%